Постать Максима Славінського у контексті українських та міжнародних реалій першої половини ХХ століття - Мандрик, М. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
Based on the documents of former Soviet secret service, the personality of M. Slavinskyi, a diplomat, scientist and political figure, was investigated.